1989
DOI: 10.1002/bit.260340405
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐flow membrane microfiltration of a bacteriol fermentation broth

Abstract: Although cross-flow membrane filtration is a very attractive option for harvesting cells and recovering enzymes from cell homogenates, the process is not without its problems. Foremost of these is the deposit of dissolved and suspended solutes onto the membrane surface during operation. The formation of these dense and sometimes compressive sublayers (often called cakes) offers additional resistance to axial and permeate flows and often affects the retention characteristics of the process. In view of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…This is comparable to the results of Nagata et al [34] for certain ceramic membranes. The intercept was calculated to be 94.96 · 10\2; this gives a value of 4.2 kPa as the pressure required to initiate permeate flow.…”
Section: Bacteria-free Filtration Experimentssupporting
confidence: 92%
See 1 more Smart Citation
“…This is comparable to the results of Nagata et al [34] for certain ceramic membranes. The intercept was calculated to be 94.96 · 10\2; this gives a value of 4.2 kPa as the pressure required to initiate permeate flow.…”
Section: Bacteria-free Filtration Experimentssupporting
confidence: 92%
“…It is customary in the analysis of cross-flow microfiltration using resistance models to define a ''permeability coefficient -P.C.'' as the slope of such a graph [33,34], based on the equation:…”
Section: Bacteria-free Filtration Experimentsmentioning
confidence: 99%
“…Both remain essentially unaffected by cell concentration between 2 and 4.5 g L −1 , in contrast to results of Nagata et al (1989) who observed a flux decay in conventional crossflow filtration. Initial increase in permeate and mass fluxes may be due to increase in shear stress due to concentration.…”
Section: Effect Of Cell Concentrationcontrasting
confidence: 81%
“…However, bacterial suspensions are notorious for fouling membranes, either by clogging the pores with cellular debris (Kroner et al, 1984), or by adsorption of dissolved matter or by formation of a highly compressible layer on the membrane (Nagata et al, 1989). This fouling produces a rapid decline of permeate flux and polymer transmission (Haarstrick et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…More seriously fouling large molecule might have been formed by the interaction. Nagata et al (1989) [16] already reported on a case of interaction among medium components that potassium ammonium phosphate precipitate was formed during the steam sterilization of peptone salts growth medium. The precipitate was considered as the major foulant in harvesting of B. polymyxa by membrane micro®ltration.…”
Section: Influence Of Concentrations Of Glucose and Yeast Extractmentioning
confidence: 99%